Investigação da rota biohidrometalúrgica com Acidithiobacillus ferrooxidans/thiooxidans para recuperação do cobalto de baterias de íons lítio descartadas - Santana, Laiane Kalita de (2016)
The recycling of metals from secondary sources can be advantageous. Among the metals of interest, we have cobalt, a metal used for various purposes. As regards the secondary sources of cobalt, the lithium-ion batteries can be considered, since they contain cobalt oxide in their composition (LiCoO2). This way, the objective of this work was to use the microorganism strains (Acidithiobacillus ferrooxidans and Acidithiobacillus thiooxidans) to bioleach the LiCoO2 extracted from discarded lithium ion batteries with emphasis on the recovery of cobalt for synthesis of new materials of interest. The lineage growth occurred in T&K medium and the growth investigation was made by observing the media, by platelet growth and microscope analysis. Then, the inoculum was standardized on 5 x 106 cells mL-1 and used in bioleaching tests. The bioleaching was investigated: the microorganism nature: separate strains and A. ferrooxidans and A. thiooxidans consortium, bioleaching time (0 to 40 days), inoculum proportion (5 to 50% v/v), energy source (iron and sulfur) and residue concentration (1063 to 8500 mg L-1 of cobalt). The cobalt concentration in the media was found by atomic absorption spectrometry and the medium pH was monitored during the bioleaching. The results show that the amount of bioleached cobalt increases with time and the iron concentration. The bioleaching with A. thiooxidans was not influenced by the addition of sulfur. The use of the two lineages together did not improve the bioleaching rates. Among the lineages, the A. thiooxidans presented better results and was able to bioleach cobalt amounts above 50% in most of the experiments. A. thiooxidans presented lower bioleaching rates, with a maximum of 50% after 24 days of experiment. After reprocessing by bioleaching, the cobalt in solution was used for synthesis of new materials: such as LiCoO2 cathode and as adsorbent pesticide double lamellar hydroxide (HDL Co-Al-Cl) by the Pechini and co-precipitation methods. The reprocessed LiCoO2 presented a unique stoichiometric phase relative to the HT-LiCoO2 structure similar to the JCPDS 44-0145, presenting electrochemical activity when tested as a cathode material. The double lamellar hydroxide Co-Al-Cl was tested as pesticide adsorbent, being possible to adsorb around 100% of the pesticide. The bioleaching was efficient in the recovery of cobalt present in lithium-ion batteries and microorganisms presented high tolerance to the residue, being able to bioleach even at higher LiCoO2 concentrations. The cobalt bioleaching medium did not impair the synthesis phases and the obtained materials presented structure and activity similar to the sintered materials from the reagents containing cobalt.